KAJIAN STRATEGI KOMUNIKASI VISUAL PADA IKLAN ANIMASI SASA & HAROUSEL “SASA HADIRKAN RASA UNTUK INDONESIA” - Nisa, Fika Khoirun; Erdiana, Setya Putri (Universitas Mercu Buana, 2023)
The outbreak of the Covid-19 pandemic has had a major impact on various sectors. Likewise the advertising industry, the changes requires workers in the advertising sector to find solutions that can overcome all the limitation. One way that can be done is by implementing a visual communication strategy using materials that are not only efficient, but can also be done in a limited scope of locations, as did the Sasa brand through the animated advertisement. The analytical method used in the form of a semiotic method will begin with a discussion of the visual objects shown in the ad by paying attention to each design element used. Then the study will focus on the semiotic elements of the level of meaning which will be divided into two, namely connotative (implicit) meaning and denotative (explicit) meaning. The results of this study can be used as evaluation material and reference for visual communication strategies in designing an advertisement during a pandemic and after a pandemic, so that an animated product can be interpreted as an alternative advertising medium within the social limitations of the Covid-19 pandemic.